Expression Atlas of the Deubiquitinating Enzymes in the Adult Mouse Retina, Their Evolutionary Diversification and Phenotypic Roles. - Mariona Esquerdo; Xavier Grau-Bové; Alejandro Garanto; Vasileios Toulis; Sílvia Garcia-Monclús; Erica Millo; Ma José López-Iniesta; Víctor Abad-Morales; Iñaki Ruiz-Trillo; Gemma Marfany (PLoS ONE, 2016)
Ubiquitination is a relevant cell regulatory mechanism to determine protein fate and function. Most data has focused on the role of ubiquitin as a tag molecule to target substrates to proteasome degradation, and on its impact in the control of cell cycle, protein homeostasis and cancer. Only recently, systematic assays have pointed to the relevance of the ubiquitin pathway in the development and differentiation of tissues and organs, and its implication in hereditary diseases. Moreover, although the activity and composition of ubiquitin ligases has been largely addressed, the role of the deubiquitinating enzymes (DUBs) in specific tissues, such as the retina, remains mainly unknown. In this work, we undertook a systematic analysis of the transcriptional levels of DUB genes in the adult mouse retina by RT-qPCR and analyzed the expression pattern by in situ hybridization and fluorescent immunohistochemistry, thus providing a unique spatial reference map of retinal DUB expression. We also performed a systematic phylogenetic analysis to understand the origin and the presence/absence of DUB genes in the genomes of diverse animal taxa that represent most of the known animal diversity. The expression landscape obtained supports the potential subfunctionalization of paralogs in those families that expanded in vertebrates. Overall, our results constitute a reference framework for further characterization of the DUB roles in the retina and suggest new candidates for inherited retinal disorders.